(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2025)
In its role as a moral teaching, Confucianism can be considered a belief system or religion. Religiosity in Confucianism is more humanistic due to its greater emphasis on the humanitarian aspect. As an ideology, along with capitalism, Confucianism also has the same influence on Chinese society. However, the ethical and moral aspects emphasized in Confucianism make its position more special compared to other schools of thought. This article attempts to present a review of the values of virtue in Confucianism and its influence on the work ethic of Chinese people in Indonesia. From time to time, Confucianism remains one of the most actual and relevant teachings. This is reasonable because, in Confucianism, the values of virtue serve as the moral foundation for its adherents. These values of virtue have influenced humans to choose ethical actions. The same values have an influence on the success of Chinese people in Indonesia. Inspired by Confucian teachings, they have a work ethic that emphasizes ethical attitudes (honesty and justice), enthusiasm, and totality of work, and respect for human dignity (humanism).